Encouraging learners to Involve more in English Lessons - Alzarga, Sumaia (المجلة العلمية لكلية التربية, 2023)
Encouraging the involvement of the learner is an obvious goal for the teacher which makes the learning process more effective and interesting in the classroom. Strategies for maintaining and increasing student involvement are essential elements of creating successful learning. The student’s involvement in the lesson consists of time listening to his teacher, contributing to the discussion, doing activities and spending productive time together by asking and answering questions to practice what they have previously learned. These activities assist the learner to increase their cognitive ability and create more incentives rather than just limiting their time listening to the teacher. The purpose of this paper is to outline how the teacher motivates the learner to be involved in the lesson. In the second section, I will highlight ways to involve learners in the classroom and how to keep them interacting during doing activities. In section three, I will write about how the teacher takes into account reasons why learners do not become involved in the lesson, individual differences and needs among the students who are learning another language.